Rare Imaging of Fat Embolism Seen on Computed Tomography in the Common Iliac Vein after Polytrauma - Hojun Lee; Jonghwan Moon; Junsik Kwon; John Cook-Jong Lee (Journal of Trauma and Injury)
Fat embolism refers to the presence of fat droplets within the peripheral and lung microcirculation with or without clinical sequelae. However, early diagnosis of fat embolism is very difficult because the embolism usually does not show at the computed tomography as a large fat complex within vessels. Forty-eight-year-old male with pedestrian traffic accident ransferred from a local hospital by helicopter to the regional trauma center by two flight surgeons on board. At the rendezvous point, he had suffered with dyspnea without any airway obstruction sign with 90% of oxygen saturation from pulse oximetry with giving 15 L of oxygen by a reserve bag mask. The patient was intubated at the rendezvous point. The secondary survey of the patient revealed multiple pelvic bone fracture with sacrum fracture, right femur shaft fracture and right tibia head fracture. Abdominal computed tomography was performed in 191 minutes after the injury and fat embolism with Hounsfield unit of −86 in his right common iliac vein was identified. Here is a very rare case that mass of fat embolism was shown within common iliac vein detected in computed tomography. Early detection of the fat embolus and early stabilization of the fractures are essential to the prevention of sequelae such as cerebral fat embolism.